2020
DOI: 10.3390/antibiotics9050219
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics: A Bibliometric Analysis of Top 100 Classics

Abstract: Citation frequencies represent the most significant contributions in any respective field. This bibliometric analysis aimed to identify and analyze the 100 most-cited publications in the field of antibiotics and to highlight the trends of research in this field. “All databases” of Clarivate Analytics’ Web of Science was used to identify and analyze the 100 publications. The articles were then cross-matched with Scopus and Google Scholar. The frequency of citation ranged from 940 to 11,051 for the Web of Scienc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 130 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Hence, the impact of published articles is assessed after at least after 5 years of publication. As highlighted, an increase in the age of publication positively influenced the citation frequency (68). Hirsch announced the h-index in 2005 and subsequently, it became a very popular bibliometric meas- ure (69).…”
Section: Most Relevant Journals and Subject Categoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the impact of published articles is assessed after at least after 5 years of publication. As highlighted, an increase in the age of publication positively influenced the citation frequency (68). Hirsch announced the h-index in 2005 and subsequently, it became a very popular bibliometric meas- ure (69).…”
Section: Most Relevant Journals and Subject Categoriesmentioning
confidence: 99%
“…In addition, since the use of citation indicators as performance indicators, researchers know that their references may influence the careers of the researchers they cite (77). The trend analysis of the influence of age of publication on the citation density showed that certain topics after reaching maturity show a decrease in citation density (68). It has been described that the real impact of a publication can only be evaluated at least two decades after it has been published (68,78).…”
Section: Most Relevant Journals and Subject Categoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bibliometric analysis may be used by researchers to examine and assess publications on medical research, including fields such as infectious diseases [ 14 , 15 , 16 , 17 ] or dentistry [ 18 , 19 , 20 , 21 ]. In recent years, endodontics has also been the object of Scientometric and/or bibliometric studies, analyzing scientific output globally [ 22 ], or in a specific field, such as regenerative endodontics [ 23 ], micro-CT [ 24 ], or vital pulp therapy [ 25 ].…”
Section: Introductionmentioning
confidence: 99%